What Does Theory of Moves Enable that Classical Game Theory Could Not? a Study on Methodological Tools of Theory of Moves - Aktaş, Özgür (Muş Alparslan Üniversitesi, 2021)
Oyun Teorisi ve oyun teorisi modelleri uzun yıllardır bilhassa uluslararası siyaseti ve rasyonel aktörlerin stratejik etkileşimlerini irdelemek, genel olarak sosyal dünyanın dinamiklerini incelemek için kullanılmaktadır. Oyun Teorisi’nin açıklayıcı kapasitesini geliştirmek için çeşitli modeller ve yaklaşımlar geliştirilmektedir. Bu bağlamda Hareketler Teorisi stratejik etkileşimleri daha gerçekçi bir şekilde inceleyip açıklayabilmek için Stephen Brams tarafından geliştirilmiştir. Bu makalenin amacı, Hareketler Teorisi’nin temel varsayımları, kuralları ve kavramlarını, Klasik Oyun Teorisi’nin yapısı ve kısıtlarıyla bir arada inceleyerek Hareketler Teorisi’nin sağladığı metodolojik araçları değerlendirmektir. Hareketler Teorisinin Oyun Teorisi’ne yaptığı dikkate değer katkılar olduğu savunulurken, Hareketler Teorisi’nin kendi metodolojik kısıtlarına da dikkat çekilmiştir.

Game Theory (GT) and game-theoretic models have been used for many years to examine particularly international politics and strategic interactions between rational actors, in general, the dynamics of the social world. Different models and approaches have been developed to enhance the explanatory capacities of GT. In this regard, Theory of Moves (TOM) was developed by Stephen Brams in order to analyze and explain strategic interaction more realistically. The purpose of this article is to examine the main assumptions, rules and concepts of TOM with the structure and drawbacks of Classical GT to evaluate methodological tools of TOM. The purpose of this article is to examine two game-theoretic models, Classical GT and TOM, and to scrutinize what sorts of methodological utilities could be achieved by them. Thus it is aimed to illustrate methodological constraints and drawbacks of Classical GT and how the rules and features of TOM intend to overcome these issues. In the study, although it is claimed that TOM made remarkable contribution to GT, the methodological constraints of TOM are pointed out.
Hareketler Teorisi Klasik Oyun Teorisinin Sağlayamadığı Neyi Sağlıyor? Hareketler Teorisinin Metodolojik Araçları Üzerine Bir Çalışma
anemon
Keywords: Hareketler Teorisi; Klasik Oyun Teorisi; Oyun Teorisi; Mahkumun İkilemi; Theory of Moves; Classical Game Theory; Game Theory; Prisoner’s Dilemma